Time-resolved MR angiography for detecting and grading ovarian venous reflux: comparison with conventional venography - Yang, D M (The British Institute of Radiology., 2012)
OBJECTIVE: The purpose of this study was to compare the diagnostic accuracy of time-resolved MR angiography (TR-MRA) with that of conventional venography for the detection and grading of ovarian venous reflux, which aid in the diagnosis of pelvic venous congestion. METHODS: We performed a retrospective analysis of 19 consecutive patients who underwent TR-MRA and conventional venography. The images were analysed by two radiologists in a randomised “blinded” manner. With the use of conventional venography as a gold standard, the images were reviewed to determine if differences in the detection and grading of ovarian venous reflux were seen between TR-MRA and conventional venography; the sensitivity, specificity and accuracy of TR-MRA compared with that of conventional venography were evaluated. The McNemar test was performed to determine the significance of any differences. Interobserver agreement was analysed using generalised κ statistics. RESULTS: There was no significant difference between TR-MRA and conventional venography for grading ovarian venous reflux (p>0.05). The sensitivity, specificity and diagnostic accuracy of TR-MRA were found to be 66.7%, 100% and 78.9%, and 75%, 100% and 84.2%, respectively, for the two observers. The weighted κ-values indicated excellent agreement between the two observers for grading ovarian venous reflux on TR-MRA (κ=0.894). CONCLUSION: TR-MRA is an accurate method for accessing pelvic venous congestion.